Multi-scale mechanistic elucidation of hydrogen generation in chemical looping gasification of lignite using carbide slag - Xujie Luo; Senlin Dong; Jie Yang; Binbin He; Dongyang Li; Liping Ma; Bing Huang; Liang Chen; Qihong Cen; Heping Zeng; Rui Nie; Lan Shao (Journal of Environmental Chemical Engineering, 2026)

Numerical analysis of heterogeneous reservoir erosion induced by hydrate dissociation from granular rearrangement perspective - Rui Zhou; Yang Liu; Bing Bai (Computers and Geotechnics, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

Pore-scale investigation of pore structure characteristics and their impact on thermo-hydraulic coupled transport in unsaturated bentonite: From fractal reconstruction to direct numerical simulation - Guangchang Yang; Xin Gong; Bo Zhang; Rui Zhou; Yang Liu; Bing Bai (Computers and Geotechnics, 2026)

Quantifying land-use-specific non-point source pollution in a forest-dominated watershed using control-section mass balance and ridge regression - Zhang Jing; Zhao Rui-rui; Yang Lu Ping; Chen Zi Jing; Xing Bing; Peng Shi-tao (Process Safety and Environmental Protection, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Excavation Damage Evaluation of Rock Anchor Beam Based on Acoustic P-Wave Velocity and RFD Index in Highly Stressed Powerhouse: A Case Study of Baihetan Hydropower Station, China - Jin-Shuai Zhao; Lei Xia; Yong Fan; Quan Jiang; Bing-Rui Chen; Guang-Dong Yang; Dong-Ze Wang (Rock Mechanics and Rock Engineering, 2026)

Quantitative source apportionment of soil geochemical elements in a typical mountain-plain transition zone, northern China: the combined influence of geological background and anthropogenic activities - Huan Li; Yi-Xuan Zhang; Yang Yao; Qin-Rui Zhang; Bo Zhang; Yong-Wei Zhao; Bing Han; Guo-Li Yuan (Environmental Geochemistry and Health, 2026)

Impact Mechanical Behavior and Energy Dissipation Analysis of Rock-Concrete Composites with different Interface Roughness - Wei-jing Yao; Han-bing Xu; Sheng-qi Yang; Shao-ge Rui; Jian-yong Pang (Applied Geophysics, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

The association of long-term exposure to PM1 with dyslipidemia in Chinese older adults and the modifying role of vitamin D - Pengjing Yao; Rui Zhang; Xuqiu Cheng; Xinyu Kou; Ziwei Tian; Jinmin Zheng; Yan Zhang; Xianwei Guo; Bing Hu; Changliu Liang; Yufeng Wen; Fangbiao Tao; et al. (Atmospheric Pollution Research, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

A novel dual-mode sensor based on green-synthesized AuNPs and natural nitrogen-doped CQDs for tobramycin detection: enhanced sensitivity and specificity - Qiang Li; Rui-ling Yin; Xing-yi Yang; Yi-xin Xu; Yan-bing Leng; Xin Liu (Food Research International, 2026)

THMC multi-field coupled constitutive model for unsaturated soils incorporating salinity effects - Guangchang Yang; Mengying Zhou; Jianping Liu; Rui Zhou; Yang Liu; Bing Bai (Computers and Geotechnics, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Improving the depression selectivity of fulvic acid for the efficient upgrading of phosphate ores based on nitrification modification: Flotation performance and mechanism insights - Rui Ma; Bingqiao Yang; Yifan Zhang; Bing Deng (Minerals Engineering, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Biomass pyrolysis characterisation based on machine learning: identification of key factors affecting biochar stability - Peng Zhang; Bing Wang; Hui Liu; Yang Rui; Guomin Li; Jian Zhang (Biomass and Bioenergy, 2025)

Impact of thallium contamination on microbial communities and biogeochemical cycles in freshwater ecosystems - Shuang Yan; Yongxin Bing; Qianli Ma; Rui Zhao; Xiaodie Cai; Yuyin Yang; Sili Chen; Shuguang Xie (Aquatic Ecology, 2025)

Spatiotemporal evolution and driver analysis of wastewater greenhouse gas emissions in Chinese mainland: Insights and future trends - Yang Chen; Rui Qiu; Min Zheng; Bing-Jie Ni; Hong-Guang Guo (Environmental Research, 2025)

Interactions and feedback mechanisms in oasis wetland hydrology–soil–vegetation systems, northwestern China - Bing Liu; Ying Zhao; Arash Malekian; Xiao Wang; Wenzhi Zhao; Maliheh Behrang Manesh; Bin Wang; Changkun Yang; Weihao Sun; Wen Li; Pouyan Dehghan Rahimabadi; Yangyang Meng; et al. (CATENA, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The efficient separation of apatite and dolomite using sodium dextran sulphate as an eco-friendly depressant: Flotation performances and atom-scale interaction mechanism - Rui Ma; Bingqiao Yang; Bing Deng; Hui Shao; Yimei Xiao; Huihua Luo (Minerals Engineering, 2025)

Chemical constituents from the stems of Erythropalum scandens - Qiao-dan Pan; Yuan-he Huang; Li-yang Zhao; Wei-rui Wang; Bing-an Wei; Ying-ying Xu; Xian Wei (Phytochemistry Letters, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Experimental and numerical investigation on the superheated and subcooled ammonia spray characteristics under high injection pressure - Rui Yang; Heng Liu; Bing Li; Qinglong Tang; Mingfa Yao (Fuel, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Unraveling Neurotoxicity Discrepancies: Comparative In vitro and In vivo Analysis of Colistin and Polymyxin B and the Underlying Mechanisms - Rui Yang; Debiao Xiang; Fang Yuan; Yuan Yang; Pengkai Wang; Bing Xu; Xin Li (Molecular Neurobiology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

ANFIS-Based Course Controller Using MMG Maneuvering Model - Yu Guo; Rui Yang; Zhiheng Zhang; Bing Han (Journal of Marine Science and Engineering, 2025)
In the domain of course control, traditional methods such as proportional–integral–derivative (PID) control often exhibit limitations when addressing complex nonlinear systems and uncertain disturbances. To mitigate these challenges, the adaptive neuro-fuzzy inference system (ANFIS) has been integrated into course control strategies. The primary objective of this study is to investigate the course control characteristics of vessels governed by the ANFIS controller under both normal and severe sea conditions. A three-degree-of-freedom (3-DOF) maneuvering model set (MMG) was employed and validated through sea turning tests. The design of the ANFIS controller involved a combination of the backpropagation algorithm with the least square method. Training data for the ANFIS control system were derived from a linear control framework, followed by simulation tests conducted under normal and severe sea conditions to assess control performance. The simulation results indicate that in normal sea conditions, ANFIS has more stable heading control (smaller Aψ), but at the cost of more energy consumption (larger Iδ). Notably, response time is reduced by approximately 36.7% compared to that of the linear controller. Conversely, during severe sea conditions, ANFIS exhibits an increase in response time by about 33.3% relative to the linear controller while maintaining a smaller Iδ. In the whole course control stage, the stability is better than the linear controller, and it has better energy-saving characteristics. Under scenarios involving small and large course alterations, Aψ values for ANFIS are approximately 11.28% and 13.97% higher than those observed with the best-performing linear controller (λψ = 60), respectively. As the propeller speed increases, the Aψ value of the ANFIS controller decreases significantly, to about 62.71%, indicating that the energy efficiency is improved and the course stability is also enhanced. In conclusion, it can be asserted that the implementation of an ANFIS controller yields commendable performance in terms of controlling vessel courses effectively.

A TiO2/ZnO (nanoparticle/quantum dot) heterojunction with strong interfacial coupling for ultrasensitive SERS sensing of antibiotic residues in environment (water and soil) and their efficient degradation - Yimin Tang; Xuewei Zhang; Rui Wang; Huizhu Zhang; Libin Yang; Xin Jiang; Bing Zhao (Journal of Environmental Chemical Engineering, 2025)

A novel g-C3N4/TiO2 heterojunction for ultrasensitive detection of bisphenol A residues - Xin Jiang; Han Jiang; Yimin Tang; Rui Wang; Wenxue Wang; Libin Yang; Bing Zhao (Food Chemistry, 2025)

Two novel butyrolactone lignan dimers from leaves of Castanopsis chinensis and their anti-inflammatory activities - Ya-Feng Wang; Ping Lin; Nao Pang; Zhang-Bin Liu; Bing-Yuan Yang; Rui-Jie He; Yong-Lin Huang (Journal of Natural Medicines, 2025)

Hydrothermal carbonization of woody waste: Changes in the physicochemical properties and the structural evolution mechanisms of hydrochar during this process - Cong Yang; Peng Xia; Lingyun Zhao; Ke Wang; Bing Wang; Rui Huang; Huan Yang; Yuanzhu Yao (Chemosphere, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Cytotoxicity sesquiterpenoids from the leaves of Datura stramonium L. - Juan Pan; Yan Liu; Ao-Fei Wang; Jia-Tong Wu; Rui Yang; Wei Guan; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Triterpene hexahydroxydiphenoyl ester and phenol glucosides from the leaves of Castanopsis eyrie (Champ. ex Benth.) Hutch - Bing-Yuan Yang; Nao Pang; Rui-Jie He; Ya-Feng Wang; Yong-Lin Huang (Natural Product Research, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Does digital economy curb carbon intensity? New insights from China - Rui Yang; Bing Chen; Jing Wu (Environmental Science and Pollution Research, 2023)

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Soil organic carbon stock in China’s tea plantations and their great potential of carbon sequestration - Dan Wang; Bing Sheng Wu; Fei Li; Xuqing Li; Zhihui Wang; Jianfeng Hou; Rui Cao; Wanqin Yang (Journal of Cleaner Production, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Effects of Snail Bellamya purificata Farming at Different Stocking Densities on the Algal and Fungal Communities in Sediment - Yiran Hou; Mengmeng Zhou; Rui Jia; Wei Sun; Yanhong Yang; Xiongjian Huang; Bing Li; Jian Zhu (Fishes, 2023)
The snail Bellamya purificata is recognized as a potential bio-remediation species, and is commonly employed in polyculture to enhance resource utilization efficiency and realize culture environment regulation. In order to enrich the microbiome studies on elucidating the ecological effects of snail B. purificata farming, we assessed the effect of B. purificata farming activities, at varying stocking densities, on the algal and fungal communities in sediment. Four experimental groups were established in our study, each corresponding to a different stocking density: 0, 234.38, 468.75, and 937.5 g/m2, represented as CON, LD, MD, and HD, respectively. High-throughput sequencing based on ITS and 23S ribosomal RNA (rRNA) genes was employed to analyze the variations in algal and fungal communities under B. purificata farming activities at different stocking densities. B. purificata farming activities had no significant effect on the alpha diversities of fungal and algal communities, but significantly altered the compositions of fungal and algal communities in sediments, especially B. purificata farming activity at low stocking density. B. purificata farming activities at low stocking density could significantly increase the relative abundances of fungal genera Paraconiothyrium and Penicillium compared with the CON group. The promoting effect diminished with increasing density. B. purificata farming activities at low or medium stocking density also could enhance the relative abundances of algal genera Microchloropsis, Scenedesmus, and Auxenochlorella. Hence, B. purificata farming activity at low stocking density might be the optimum density to enhance resource utilization efficiency and minimize environmental pollution.

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

An empirical study of the design of an ecological damage compensation assessment framework for land reclamation from the sea - Wang Tao; Yang Lu; Deng Lijing; Yin Yue; Xin Bing; Zhao Rui (Journal of Coastal Conservation, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Changes in PM2.5-related health burden in China's poverty and non-poverty areas during 2000–2020: A health inequality perspective - Yan Li; Baojie Li; Hong Liao; Bing-Bing Zhou; Jing Wei; Yuxia Wang; Yuzhu Zang; Yang Yang; Rui Liu; Xiaorui Wang (Science of The Total Environment, 2023)

Flavonoids and other phenolics from Camellia nitidissima chi flowers - Zhennan Wang; Bing Sun; Rui Yang; Ai-Qun Jia (Natural Product Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The constitutive behavior and dissociation effect of hydrate-bearing sediment within a granular thermodynamic framework - Bing Bai; Rui Zhou; Guangchang Yang; Weilie Zou; Wei Yuan (Ocean Engineering, 2023)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Mild encephalitis/encephalopathy with a reversible splenial lesion associated with respiratory syncytial virus infection in infants - Xue-Lin Li; Jinming Han; Zhong-Rui Yan; Bing-Wei Zhang; Hai-Yang Wang (Journal of NeuroVirology, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

How the variations of terrain factors affect the optimal interpolation methods for multiple types of climatic elements? - Bing Guo; Fei Yang; Hongwei Wu; Rui Zhang; Wenqian Zang; Cuixia Wei; Guangmao Jiang; Chao Meng; Huihui Zhao; Xiaoyan Zhen; Dafu Zhang; Hailing Zhang (Earth Science Informatics, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

A new sesquiterpenoid with cytotoxic and anti-inflammatory activity from the leaves of Datura metel L - Rui Guo; Yan Liu; Juan Pan; Wei Guan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

An Ordovician carbonate reservoir in strike-slip structures producing from fault-associated fracture systems, 3D seismic region of Northern Shun 8 block (Tarim Basin) - Li Bing; Zhao Rui; Kong Qiangfu; Deng Shang; Li Huili; Yang Weili; Zhang Zhongpei (Carbonates and Evaporites, 2019)

Effects of organic-inorganic amendments on the cadmium fraction in soil and its accumulation in rice (Oryza sativa L.) - Bing Li; Lan Yang; Chang Quan Wang; Shun Qiang Zheng; Rui Xiao; Yong Guo (Environmental Science and Pollution Research, 2019)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Spatial distribution of soil cadmium and its influencing factors in peri-urban farmland: a case study in the Jingyang District, Sichuan, China - Bing Li; Rui Xiao; Changquan Wang; Linhai Cao; Yi Zhang; Shunqiang Zheng; Lan Yang; Yong Guo (Environmental Monitoring and Assessment, 2017)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

A Microseismic Method for Dynamic Warning of Rockburst Development Processes in Tunnels - Guang-Liang Feng; Xia-Ting Feng; Bing-rui Chen; Ya-Xun Xiao; Yang Yu (Rock Mechanics and Rock Engineering, 2015)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)